2010
DOI: 10.1038/gt.2010.128
|View full text |Cite
|
Sign up to set email alerts
|

AAV2-mediated transfer of the human aquaporin-1 cDNA restores fluid secretion from irradiated miniature pig parotid glands

Abstract: Previously (Shan et al, 2005), we reported that adenoviral vector-mediated transfer of the human aquaporin-1 (hAQP1) cDNA to minipig parotid glands following irradiation (IRti) transiently restored salivary flow to near normal levels. This study evaluated a serotype 2, adeno-associated viral (AAV2) vector for extended correction of IR (single dose; 20 Gy)-induced, parotid salivary hypofunction in minipigs. Sixteen weeks following IR, parotid salivary flow decreased by 85-90%. AAV2hAQP1 administration at week 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 32 publications
2
59
0
1
Order By: Relevance
“…Previously, we developed a mouse model of BRONJlike disease [6]; however, well-established large-animal models are needed for preclinical studies and will provide researchers with the opportunity to elucidate the mechanisms underlying BRONJ and to explore potential therapeutic approaches, particularly those that are difficult to implement in small-animal models such as rodents due to the small size of the orofacial region. Because of the high similarity between swine and humans in terms of histology and functions of the orofacial tissues [8,11,12], the miniature pig is increasingly used as a large-animal model for a variety of biomedical studies [13,14]. The findings from the present study showed that ZA treatment can suppress Treg levels in peripheral blood while increasing the levels of gdT cells and IL-17 in peripheral blood.…”
Section: Discussionsupporting
confidence: 59%
“…Previously, we developed a mouse model of BRONJlike disease [6]; however, well-established large-animal models are needed for preclinical studies and will provide researchers with the opportunity to elucidate the mechanisms underlying BRONJ and to explore potential therapeutic approaches, particularly those that are difficult to implement in small-animal models such as rodents due to the small size of the orofacial region. Because of the high similarity between swine and humans in terms of histology and functions of the orofacial tissues [8,11,12], the miniature pig is increasingly used as a large-animal model for a variety of biomedical studies [13,14]. The findings from the present study showed that ZA treatment can suppress Treg levels in peripheral blood while increasing the levels of gdT cells and IL-17 in peripheral blood.…”
Section: Discussionsupporting
confidence: 59%
“…The results are cautiously encouraging for the treatment of IR-induced xerostomia with patients in RTOG grades 2 and 3. Because Ad5 vectors do not result in permanent gene transfer, our findings represent an important proof-of-concept and suggest further study of hAQP1 gene transfer with less immunogenic vectors; for example, serotype 2 adeno-associated virus, capable of longer-lived expression in salivary glands (15), are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…We do not yet understand why subject #40 failed to experience subjective benefit from AdhAQP1 treatment, despite a measurable biologic effect. The lack of response caused by inflammation or Ad5 reactivation and RCA formation could be circumvented by using another vector-delivery system (e.g., based on a serotype 2, adeno-associated virus) (15). Overall, the proportion of responders seen herein is not surprising, given findings from previous phase I gene-therapy studies using Ad5 vectors in diverse tissues, such as the eye, heart, peripheral vasculature, and lung (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
“…Aqp gene transfer is a promising concept, which has been shown to be efficacious in rats, pigs, and finally a small group of patients who were treated with adenoviral-mediated transfer of the Aqp-1 cDNA as a treatment for radiation-induced salivary hypofunction. 12,13,43 Similar Aqp gene transfer may be adapted as a treatment for hydrocephalus, by increasing the number of AQP4 channels to help mediate water balance in the ventricular system. Although not clear if applicable to the ventricular AQP4, studies have shown increased AQP4 expression secondary to nitric oxide and lipopolysaccharide in neural tissue.…”
Section: +mentioning
confidence: 99%